Chronic Alcohol Consumption Promotes Diethylnitrosamine-Induced Hepatocarcinogenesis via Immune Disturbances - Guoxiu Yan (Nature Portfolio, 2017)
Abstract Chronic alcohol consumption increases the risk of hepatocellular carcinoma (HCC). However, little is known about the potential immunological mechanisms by which ethanol affects tumor progression. Here, adult male mice were administered multiple doses of diethylnitrosamine (DEN). Four and a half months later, the DEN-treated mice were placed on a liquid Lieber-DeCarli control diet or diet containing 5% ethanol for 2.5 months. At the end of the study, liver tissue samples were obtained to analyze pathology, gene expression, and hepatic mononuclear cells (MNCs). Results showed that ethanol feeding exacerbates the progression of hepatic tumors (characterized by the ratio of liver weight to body weight, and the tumor volume and diameter) in DEN-treated mice. Mechanistically, chronic alcohol consumption decreased the number of antitumor CD8+ T cells but increased the number of tumor-associated macrophages (TAMs) in the liver in DEN-initiated tumorigenesis. Besides, TAMs were prone to be M2 phenotype after alcohol consumption. Moreover, chronic alcohol consumption aggravated inflammation, fibrosis, and epithelial-mesenchymal transition (EMT) in the pathological process of HCC. These data demonstrate that chronic alcohol consumption exacerbates DEN-induced hepatocarcinogenesis by enhancing protumor immunity, impairing antitumor immunity and aggravating hepatic pathological injury. Targeting the immune system is a potential therapeutic regimen for alcohol-promoted HCC.